Citizen brief: Enhancing the delivery of comprehensive care for people living with HIV in Canada - Wilson, MG; Mattison, CA; Gao, C; Kendall, CE; Lavis, JN (My University, 2019)
A plain-language synthesis of what is known based on the best available global and local research evidence about the problem(s) related to enhancing the delivery of comprehensive care for people living with HIV in Canada, elements of a potentially comprehensive approach for addressing it, and key implementation considerations. This citizen brief was prepared to inform three citizen panels.
Keywords: HIV; comprehensive care; Canada